Carbon Dioxide as a Risky Asset - Adam Michael Bauer; Cristian Proistosescu; Gernot Wagner (Center for Economic Studies and ifo Institute (CESifo), 2023)
We develop a financial-economic model for carbon pricing with an explicit representation of decision making under risk and uncertainty that is consistent with the Intergovernmental Panel on Climate Change's sixth assessment report. We find that this approach provides economic support for the warming targets in the Paris Agreement across a variety of specifications. We show that risk associated with high damages in the long term leads to stringent mitigation of carbon dioxide emissions in the near term. Our results provide insight into how a systematic incorporation of climate-related risk influences 'optimal' emissions abatement pathways.
Keywords: G00; G12; Q51; Q54; 330; climate risk; asset pricing; cost of carbon